THE DISTRIBUTION OF RADIOGENIC HEAT PRODUCTION AS A FUNCTION OF DEPTH IN THE SIERRA NEVADA BATHOLITH, CALIFORNIA - Brady R.J.; Ducea M.N.; Kidder S.B.; Saleeby J.B. (My University, 2006)
Geochemical analyses and geobarometric determinations have been combined to create a depth vs. radiogenic heat production database for the Sierra Nevada batholith, California. This database shows that mean heat production values first increase, then decrease, with increasing depth. Heat production is ~2 μW/m3 within the ~3-km-thick volcanic pile at the top of the batholith, below which it increases to an average value of ~3.5 μW/m3 at ~5.5 km depth, then decreases to ~0.5-1 μW/m3 at ~15 km depth and remains at these values through the entire crust below 15 km. Below the crust, from depths of ~40-125 km, the batholith's root and mantle wedge that coevolved beneath the batholith appears to have an average radiogenic heat production rate of ~0.14 μW/m3. This is higher than the rates from most published xenolith studies, but reasonable given the presence of crustal components in the arc root assemblages. The pattern of radiogenic heat production interpreted from the depth vs. heat production database is not consistent with the downward-decreasing exponential distribution predicted from modeling of surface heat flow data. The interpreted distribution predicts a reasonable range of geothermal gradients and shows that essentially all of the present day surface heat flow from the Sierra Nevada could be generated within the ~35 km thick crust. This requires a very low heat flux from the mantle, which is consistent with a model of cessation of Sierran magmatism during Laramide flat-slab subduction, followed by conductive cooling of the upper mantle for ~70 m.y. The heat production variation with depth is principally due to large variations in uranium and thorium concentration; potassium is less variable in concentration within the Sierran crust, and produces relatively little of the heat in high heat production rocks. Because silica content is relatively constant through the upper ~30 km of the Sierran batholith, while U, Th, and K concentrations are highly variable, radiogenic heat production does not vary directly with silica content. © 2005 Elsevier B.V. All rights reserved.
Keywords: GEOTHERMAL GRADIENT; HEAT FLOW; HEAT PRODUCING ELEMENTS; HEAT PRODUCTION; SIERRA NEVADA